(untitled) (Journal of actual problems of jurisprudence, 2018)
This article discusses the legal regulation of immigration for family reunification. We consider immigration legislation of the Republic of Kazakhstan. The analysis of foreign experience in managing migration for family reunification. Particular attention is paid to the definition of the family as the foundation of modern society and one of the basic human rights. Keywords: migration, family reunification, immigration, emigration, family, immigration law, human rights.